An approach for prevention planning based on the prevalence and comorbidity of neurodevelopmental disorders in 6-year-old children receiving primary care consultations on the island of Menorca - Lorena Francés; Jessica Caules; Antoni Ruiz; Catalina Virgínia Soler; Amaia Hervás; Alberto Fernández; Alberto Rodríguez-Quiroga; Javier Quintero (BMC, 2023)
Abstract Background Few studies have estimated the real prevalence of neurodevelopmental disorders according to the Diagnostic and Statistical Manual of Mental Disorders, 5th Edition (DSM-5) in Spain and worldwide. However, there are disparate prevalence figures. We consider research in this field essential to improve early detection, secondary prevention, and health planning. Methods The Minikid ADHD and TICS-Mini International Neuropsychiatric Interview for Children and Adolescents, the Autism Spectrum Quotient (Children's version, AQ- Child) and a protocol of general medical questions were administered for screening purposes. The PROLEXIA battery for children aged from 4 to 6 years was used for direct assessments. Parents provided information on emotional, medical, and school aspects. The final population evaluated using these tools consisted of 291 6-year-old subjects. Results The overall risk of presenting with a neurodevelopmental disorder was 55.4%. A 23.4% risk of presenting with attention-deficit/hyperactivity disorder (ADHD) in any modality (inattentive, hyperactive-impulsive and combined), a 2.8% risk of developing autism spectrum disorder (ASD), a 30.6% risk of presenting with a learning disorder with reading difficulties, a 5.5% risk of tics and a 22.5% risk of language problems (incomprehensible language or minor language problems) were detected in the sample. The most common combination of disorders was learning and language difficulties, accounting for 6.9% of the sample. The second most frequent combination was the presence of learning and language difficulties and ADHD, accounting for 4.5% of the sample. Conclusions The prevalence of risks detected in our sample seems to be consistent with national and international studies. A significant proportion of our sample had never been previously diagnosed (85%), so early detection programs are recommended.